2013
DOI: 10.1038/srep02258
|View full text |Cite|
|
Sign up to set email alerts
|

GSTM1 and GSTT1 null polymorphisms and male infertility risk: an updated meta-analysis encompassing 6934 subjects

Abstract: Published data on the association between the GST genes polymorphisms and male infertility risk are inconclusive. We investigated GST genes polymorphisms in a large sample size case-control study, and conducted a literature-based meta-analysis of 6934 individuals. Our case-control study showed the GSTM1 null genotype was significantly associated with idiopathic oligozoospermia, while the null genotype of GSTT1 was significantly associated with normozoospermia and azoospermia. Additionally, significantly elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
2
31
1
3
Order By: Relevance
“…No. of Pages 5 deficiencies in humans (Aston and Carnell, 2009;Aston et al, 2010;Sang et al, 2011;Hu et al, 2011;Wu et al, 2013;Xu et al, 2013). Genes underlying the volume of semen and total number of sperm in ejaculate of fertile bulls were not studied.…”
Section: Introductionmentioning
confidence: 99%
“…No. of Pages 5 deficiencies in humans (Aston and Carnell, 2009;Aston et al, 2010;Sang et al, 2011;Hu et al, 2011;Wu et al, 2013;Xu et al, 2013). Genes underlying the volume of semen and total number of sperm in ejaculate of fertile bulls were not studied.…”
Section: Introductionmentioning
confidence: 99%
“…• 367 testis and epididymis specific hypomethylated genes • 134 hypermethylated [11] Global OAT (69)…”
Section: Line1mentioning
confidence: 99%
“…Recently, some copy number variations (CNV) have been described to be associated with severe oligozoospermia or Sertoli-cell-only (SCO) syndrome or both [6]. In addition, some autosomal deletions, rare X-linked CNV, DNA repair mechanism defects, Y-linked syndromes, and some single nucleotide polymorphisms (SNPs) have been found to be associated with male factor infertility [7][8][9][10][11][12][13]. Although some specific mutations have been identified, other factors responsible for the sperm defects remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Most findings confirmed its influence on sperm concentrations (Aydemir et al, 2007;Finotti et al, 2009;Olshan et al, 2010) but also on sperm motility and increased oxidative damage of sperm plasma membrane in idiopathic infertility patients with GSTM1 null genotype (Aydemir et al, 2007). GSTM1 null genotype has also been studied in relation to susceptibility to male infertility, particularly to idiopathic oligozoospermia (Wu et al, 2013) and oligoasthenoteratoa zoospermia (OAT) (Tang et al, 2012). Lakpour et al (2013) indicated however no associations between GSTM1 polymorphism and sperm parameters and seminal plasma antioxidant levels in infertile men with OAT.…”
Section: Discussionmentioning
confidence: 75%